Population Genetics of Konosirus punctatus in Chinese Coastal Waters Inferred From Two mtDNA Genes (COI and Cytb) - Liu, Bingjian; Zhang, Kun; Zhu, Kehua; Shafi, Muhammad; Gong, Li; Jiang, Lihua; Liu, Liqin; Muhammad, Faiz; Lü, Zhenming (Frontiers in Marine Science, 2020)
Konosirus punctatus is important resource found in Chinese coastal waters. Two mitochondrial DNA genes were used to assess the genetic structure among twelve populations spanning all along the the Chinese coast. Fragments of 999 and 415 bp in length representing two genes (COI and Cytb) were amplified from 242 and 259 individuals, respectively. Overall, COI and Cytb showed high haplotype diversity and low nucleotide diversity. COI mtDNA gene revealed high molecular variance within populations and low variance among populations, whereas Cytb showed high variance among populations and low within population. FST values obtained for COI and Cytb showed low genetic differentiation among the populations except Zhongshan population where Cytb gene showed high FST values. The constructed phylogenetic tree and haplotype network tree does not separated twelve populations and showed a single lineage, however, Cytb gene data denoted Zhongshan population as greater difference level within population. These results increase our understanding of the genetic structure of K. punctatus and can be helpful for management of its genetic resources.